Effect of Curcumin Nanoliposomal Formulation on Cyclin E1 Expression and Cell Migration in HeLa Cells - Subandi, Subandi; Zulhaijah, Resti; Fitri, Loeki Enggar (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Cervical cancer remains a major cause of female mortality worldwide and ranks as the second-leading cause of cancer-related death among women in Indonesia, associated with Human Papillomavirus infection. HPV-driven oncogenesis disrupts cell-cycle regulation through Cyclin E1 upregulation and promotes cell migration, thereby accelerating tumor progression. Curcumin exhibits antitumor activity, but poor solubility and bioavailability limit its clinical use. Curcumin nanoliposomal formulations have been investigated to address these limitations. This in vitro study used a post-test-only control group design to evaluate a curcumin nanoliposomal formulation in HeLa cervical cancer cells. Cells received the formulations at 100, 150, and 200 μg/mL, while cisplatin 5 μg/mL served as the positive control. Cyclin E1 expression was assessed by indirect immunofluorescence and quantified using ImageJ, whereas cell migration was evaluated by scratch wound healing assay at 0 and 24 hours. Curcumin nanoliposomal formulations significantly reduced Cyclin E1 expression (p=0.006), particularly at 150 μg/mL (p=0.016) and 200 μg/mL (p=0.034). Wound closure decreased from 19.28% in the negative control to 3.42% at 200 μg/mL, although post hoc analysis showed no significant difference between treatment groups and negative control. These findings suggest that the curcumin nanoliposomal formulation warrants further validation as a potential adjunctive therapy.